Determinantes contextuais, individuais e fatores associados à perda dentária em adultos mais velhos e idosos negros - SANTOS, Lairds Rodrigues dos (2023)
Introduction: The social disadvantage of the black population is historical, whether economic or educational, resulting in limited access to essential sectors, including oral health. The elderly black population faces situations of inequalities in relation to tooth loss. Objective: This thesis is composed of two articles. The first set out to investigate the association between race and tooth loss and map the evidence on the factors associated with tooth loss in elderly black populations. The second, investigated the variables associated with tooth loss in older and older adults from quilombo remnant communities in a Brazilian state. Methodology: The Scoping Review (1st paper) was conducted in accordance with the recommendations of the Joanna Briggs Institute and PRISMA Extension for Scoping Reviews. A three-stage search strategy was applied and data were collected between April and July 2021. Searches were carried out in PubMed, Lilacsand SciELO databases. Gray literature was searched using Google Scholar (https://www.scholar.google.com/). The Cross-sectional study (2nd manuscript), was performed with quilombolas aged 50 years or older, in the Quilombo Santa Rosa dos Pretos, in Itapecuru-Mirim, Maranhão,Brazil. Socioeconomic and demographic information, profile of use of healthservices, self-perception and oral health conditions were collected (DMFT). An oral examination was performed to count the number of teeth and participants were categorized as having lost up to 12 teeth or more than 12 teeth. Fisher's exact and Chi-square tests were used to evaluate associations between the variables of interest and tooth loss. Significance level adopted was 0.05. Results: Partial loss of teeth or edentulism (1starticle) were the main conclusions completed in 80% of the studies (partial loss of teeth in 30%,edentulism in 30% and partial loss of teeth and edentulism in 20%). Most reports were originalarticles (75%), followed by research reports (15%) and dissertations (10%). We identified publications from the United States (75%), Brazil (20%) and Nigeria (5%). Quilombolas are inserted in groups with lower income (75%) and education (53,1%) (2nd article), resulting in low oral health literacy, health literature, impacting the perception of care in relation to oral health. Conclusion: Race, educational level, advanced age, and oral diseases such as periodontitis are associated with increased tooth loss in elderly Afro-descendants (1st paper).It was shown that the low of health literacy can be an intermediary factor in the behavior change of Quilombola individuals at an advanced age, resulting in higer frequency in tooth loss dueto this dysfunction over the years and a lack of perception of the need for dental treatment (2nd article).